Ultrastrong Spontaneous Surface Wetting of Room Temperature Liquid Metal on Treated Metal Surface. Issue 18 (31st August 2021) - Lin, Weiguang; Qiu, Wangkang; Tuersun, Yisimayili; Huang, Xu; Chu, Sheng
Abstract: The low melting gallium‐based liquid metal (LM) is showing tremendous potential in many technologies due to its unique properties. However, the high surface tensions as well as oxidations result in poor wetting capability on most solid surfaces, which limits its practical application. In this work, a simple chemical method is utilized to enable spontaneous wetting of LM on various metal surfaces, such as copper, nickel, and iron. It is found that LM can spread rapidly on the metal substrates treated with CuCl2 solution through reactive‐wetting and metallic bond‐enabled wetting mechanism. The redox reaction between Ga and copper compound and the formation of intermetallic compound via LM phagocytosis help drive LM to wet metal substrates spontaneously. Many factors affecting the wetting behaviors of LM, including surface roughness, crystal size, and ambient environment, are systematically studied. This finding provides a novel strategy to solve the wetting problem of LM and will enable wider applications. Abstract : A novel strategy to improve the wetting performance of liquid metal (LM) on metal substrates by means of surface modification method is reported. After the metal substrates are treated with CuCl2 solution, LM can spontaneously wet the substrates with the assistance of surface topography and ambient environment within a few minutes, via reactive‐wetting and metallic bond‐enabled wetting.